On the Complexity of Digital Video Cameras in / as Research: Perspectives and agencements - Bangou, Francis (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
The goal of this article is to consider the potential for digital video cameras to produce as part of a research agencement. Our reflection will be guided by the current literature on the use of video recordings in research, as well as by the rhizoanalysis of two vignettes. The first of these vignettes is associated with a short video clip shot by a newcomer student as part of a three-year research project that focused on the interrelationships between citizenship, technology, and pop culture. The second vignette relates to the entry of a piece of art into the research agencement. As an agencement in and of itself, the goal of this article is not to provide definitive responses, but rather to disrupt habitual ways of thinking about videos in / as research and potentially contribute to change.